Rescission of the Comprehensive Military Agreement (CMA): A Violation of International Law by South Korea? - M. Fabian Akbar; Muhammad Fathi; Javier Maramba Pandin; Andi Tenri Oddang; Muhammad Mierza Pratama (Universitas Airlangga, 2026)
This article examines the legal implications of South Korea’s suspension of the 2018 Comprehensive Military Agreement with North Korea against the background of renewed tensions on the Korean Peninsula. The study aims to determine whether this unilateral suspension is compatible with international law and what it reveals about the broader limits of lawful unilateral action in treaty relations. Using normative legal research based on doctrinal analysis, this evaluation assesses the agreement, the Vienna Convention on the Law of Treaties, relevant state practice, and official statements from both governments. The study reveals that the legality of the suspension hinges on whether North Korea’s conduct constitutes a material violation, whether there has been a fundamental change of circumstances, and how strictly national security and necessity can be invoked to justify suspending treaty obligations. The article concludes that the Korean case clarifies the boundaries between lawful countermeasures and internationally wrongful acts, and it offers normative guidance for designing and interpreting security agreements in regions marked by persistent military rivalry.